PENDEKATAN KOMUNIKATIF DALAM PENGAJARAN BAHASA ARAB - Putri Hardiyanti; Tomi Enramika; Zakiyatunnisa Al Mubarokah (Al-TARQIYAH: Jurnal Pendidikan Bahasa Arab, 2024)
This article aims to find out how the communicative approach can be used as an approach in teaching Arabic, especially in teaching Arabic for foreign speakers. The aim to be achieved in writing this article is to explain communicative language teaching related to communicative competence, the concept of language teaching with a communicative approach, assumptions, characteristics and things that are included in Arabic language teaching. The communicative approach or communicative language teaching is based on linguistic theory which states that language is a tool for communication. The communicative approach is based on the assumption that every human being has an innate ability called a "language acquisition device". Therefore, language skills are creative and are determined more by internal factors. The characteristics of the communicative approach are dynamic, contextual, and apply to spoken language, written language, and various other symbol systems and are related to theories that differentiate between competence and performance and are relative, not absolute. The advantage of this approach lies in its communicative characteristics. This approach emphasizes communication so that fluency in using language will quickly be achieved. Meanwhile, the weakness of this approach lies in its assessment. Every opportunity students are involved in activities that emphasize fluency while the assessment mostly focuses on accuracy.